2019
DOI: 10.1002/fuce.201900006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on the Degradation of La0.6Sr0.4CoO3–δ Electrodes in Dry and Humid Atmospheres

Abstract: La0.6Sr0.4CoO3–δ electrode layers with three different microstructures were manufactured by screen‐printing, spin‐coating and infiltration into a porous Ce0.9Gd0.1O1.95 backbone. Electrode performance was monitored at 700 °C in 20% O2 over periods of 1,600 to 3,860 h by means of electrochemical impedance spectroscopy under open circuit conditions. Reference measurements were performed in dry atmospheres, where significant electrode activation was observed for cells with spin‐coated and infiltrated electrodes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…However, the presence of H 2 O, especially at high concentrations required for efficient electrolysis of water, has resulted in a rapid degradation in the catalytic activity of the-state-of-the-art air electrodes, attributed largely to waterinduced surface enrichment or segregation of the A-site cations (e.g., Sr/Ba) of the electrodes. [7][8][9] Therefore, a good air electrode for R-PCECs must also have adequate tolerance to high concentrations of H 2 O, especially in the electrolysis mode when a high concentration of H 2 O is supplied. [10] To date, considerable efforts have been devoted to the exploration of highly active and durable air electrode materials/ structures for R-PCECs.…”
Section: An Efficient Bifunctional Air Electrode For Reversible Proto...mentioning
confidence: 99%
“…However, the presence of H 2 O, especially at high concentrations required for efficient electrolysis of water, has resulted in a rapid degradation in the catalytic activity of the-state-of-the-art air electrodes, attributed largely to waterinduced surface enrichment or segregation of the A-site cations (e.g., Sr/Ba) of the electrodes. [7][8][9] Therefore, a good air electrode for R-PCECs must also have adequate tolerance to high concentrations of H 2 O, especially in the electrolysis mode when a high concentration of H 2 O is supplied. [10] To date, considerable efforts have been devoted to the exploration of highly active and durable air electrode materials/ structures for R-PCECs.…”
Section: An Efficient Bifunctional Air Electrode For Reversible Proto...mentioning
confidence: 99%
“…The use of these double perovskite electrodes may increase the capital cost and the risk of delamination during thermal cycling. In addition, exposure to high partial pressures of steam may result in rapid degradation in the catalytic activity of these materials, due likely to the formation of Sr/Ba/Co-enriched surface or particles 12 14 . Therefore, a good air electrode for R-PCECs must also have sufficient tolerance against high concentrations of steam in the electrolysis mode 15 .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] However, using LSC as air electrode material in SOC cells and stacks is challenging due to the instability of its surfaces at the required operating temperatures, resulting in electrochemical performance degradation during long-term operation. 10 Several studies have shown that strontium cobaltite surfaces like LSC are prone to Sr segregation and formation of Sr-rich phases, e.g., SrSO 4 and SrCrO 4 , which result from a chemical reaction with trace impurities such as SO 2 and Cr vapors contained in the supplied air or emanating from components in the system. [10][11][12][13] A recent study has shown that the degradation on LSC surfaces already occurs from the rst exposure to ambient air and measurement conditions, indicating the effect of environmental factors on electrode stability.…”
Section: Introductionmentioning
confidence: 99%
“…10 Several studies have shown that strontium cobaltite surfaces like LSC are prone to Sr segregation and formation of Sr-rich phases, e.g., SrSO 4 and SrCrO 4 , which result from a chemical reaction with trace impurities such as SO 2 and Cr vapors contained in the supplied air or emanating from components in the system. [10][11][12][13] A recent study has shown that the degradation on LSC surfaces already occurs from the rst exposure to ambient air and measurement conditions, indicating the effect of environmental factors on electrode stability. 14 Furthermore, it has been reported that the processing and thermal history affect the long-term stability of LSC due to surface restructuring and cation redistribution.…”
Section: Introductionmentioning
confidence: 99%